2021
DOI: 10.9770/jesi.2021.9.2(2)
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' perceptions of intention to use a credit card: perceived risk and security

Abstract: The goal of this study is to combine the Technology Acceptance Model (TAM) with the theory of perceived risk to create a hypothetical model for consumer behavioral intention that will be validated using data from Saudi Arabia's intended credit card usage. 217 bank customers were polled via an online survey conducted across the country. Exploratory and confirmatory factor analyses were used to evaluate the factor structure of the measuring items, while structural equation modeling was being used to validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The study adds to the knowledge on consumer behavior by verifying the effects of perceived risk and perceived security on credit card usage intentions in Saudi Arabia, which most prior studies had ignored (Zahrani, 2021). This research may assist banks in developing new customer acquisition tactics and retaining their existing customer base by focusing on risk and security issues (Zahrani, 2021). The study also provides genuine data about Saudi Arabia's e-banking services, specifically in the credit card sector, to an academic research platform (Zahrani, 2021).…”
Section: Review Of Literaturementioning
confidence: 78%
See 4 more Smart Citations
“…The study adds to the knowledge on consumer behavior by verifying the effects of perceived risk and perceived security on credit card usage intentions in Saudi Arabia, which most prior studies had ignored (Zahrani, 2021). This research may assist banks in developing new customer acquisition tactics and retaining their existing customer base by focusing on risk and security issues (Zahrani, 2021). The study also provides genuine data about Saudi Arabia's e-banking services, specifically in the credit card sector, to an academic research platform (Zahrani, 2021).…”
Section: Review Of Literaturementioning
confidence: 78%
“…The study found that social influence, perceived usefulness, perceived ease of use, and perceived trust were all significant predictors of perceived risk and perceived security, which, in turn, affected consumer intention to use a credit card (Zahrani, 2021). The study adds to the knowledge on consumer behavior by verifying the effects of perceived risk and perceived security on credit card usage intentions in Saudi Arabia, which most prior studies had ignored (Zahrani, 2021). This research may assist banks in developing new customer acquisition tactics and retaining their existing customer base by focusing on risk and security issues (Zahrani, 2021).…”
Section: Review Of Literaturementioning
confidence: 93%
See 3 more Smart Citations